#TITLE_ALTERNATIVE# - ADITYO WIBOWO ; HASANUDDIN Z ; ABIDIN ; RWAN GUMILAR ; NIA HAERANI ; Pembimbing (1) : Prof. Dr. I
Normally 3D modelling for heritage documenting and archiving generally use reverse modeling technique. As development of TLS (Terrestrial laser scanner) technology, the reverse modeling technique become easier, faster, and accurate. In addition to create 3D model of an object, 3D modeling using TLS also creates models that are georeference in certain system. In this final assignment, the selected object is Monumen Perjuangan Rakyat Jawa Barat . Data acquisition method that is used is scanning the object by using TLS and GPS measurement to determine the coordinates of reference point. The method of data processing consist of several steps, which are registration, filtration, georeferencing, point cloud meshing, creating a surface, drawing an object, and making video of 3D model. The average error value generated by 3D model is 0.003 meters. Error value was caused by the process of nivo levelling on the laser scanner and the used target. ItÃ‚Â’s because of the nivo position on the laser scanner leveling process and target are different in each station.Comparison between 3D model result and the real object shows the differences in height and the distance in average of 1.5 cm.